Foreign wars during the reign of sultan Muhammad IV (1648-1687AD) - علاء الدين جبّور; سومر محمد فيوض (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The Ottoman Empire is one of the Turkmen states that emerged in Asia Minor in the early 13th century and the longest rule continued between the period (1299-1923) and attributes this state to its true founder Osman bin Artaghl, during which the military and political status of the Ottoman Turks was determined before that by their influence on the Islamic religion, which was widespread in Turkish environments in Central and Western Asia, which reached its peak glory in the 16th and 17th centuries. Its territory to include large parts of Asia, Africa and EuropeWith the emergence of some manifestations of weakness and reform attempts during this period and witnessed the second half of the seventeenth century tension in Ottoman-European relations, especially with Austria as a result of its violation of the Treaty of Sitavork between the two countries, which prompted the Ottoman Empire to wage war against it and ended with victory for the Ottomans and control of the most important castles of Europe, the Castle of Nohzel, the Treaty of Vashvar put an end to that war while the region of Ukraine formed the scene of the second conflict between it and Poland. Which tried to attack and control this geographical area of the Ottoman Empire but failed to do so and ended the conflict with the signing of a peace treaty known as Bojash and was later renewed under the name "Zoruna", while Russia was the Cossack revolution and work to share areas of influence in Ukraine, the reason why the Ottomans entered into conflict with Russia for the first time under Sultan Muhammad IV to end those conflicts by signing the Treaty of Ozzy.